Mengurangi Jejak Sejarah Revolusi Industri 4.0: Dari Konsep Hingga Realisasi - Kurniawan, Yudhi; Sri Pudjiarti, Emiliana (Universitas 17 Agustus 1945 Semarang, 2024)
This article discusses the Industrial Revolution 4.0 and how it impacts the world economy and society. Explains how new technologies such as artificial intelligence, blockchain technology, and the Internet of Things (IoT) have changed manufacturing systems, business operations, and human-machine interactions. Apart from that, it also discusses the social impacts arising from the Industrial Revolution 4.0 and how technological advances have influenced workplace relationships, social relationships and society in general. In addition, this paper discusses the future of education and labor in the Industrial Revolution 4.0 era. The aim is to provide readers with a broad understanding of the Industrial Revolution 4.0 and understand its deep implications, as well as consider the challenges and opportunities that lie ahead.